THE INFLUENCE OF PRICE PERCEPTION, ONLINE CUSTOMER REVIEWS, AND PROMOTIONS ON PURCHASE DECISIONS FOR FASHION PRODUCTS ON THE SHOPEE MARKETPLACE - Virda Ayu Rahmadani; Endah Budiarti (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to determine the influence of Price Perception, Online Customer Reviews, and Promotion on Purchase Decisions for Fashion Products on the Shopee Marketplace. The population in this study consists of active students from the Management Program at Universitas 17 Agustus 1945 Surabaya who have made fashion product purchases on the Shopee marketplace, with a sample of 100 respondents determined using non-probability sampling techniques. Based on the results of the SPSS version 23.0 test, the research instruments indicate that all indicators are valid and reliable. Based on the F test, all independent variables simultaneously influence purchase decisions. Based on the regression coefficient and T-test results, the variables of price perception, online customer reviews, and promotion have a positive and significant influence on purchase decisions.